Telocytes: a potential defender in the spleen of Npc1 mutant mice. Issue 5 (18th November 2016) - Zhang, Bichao; Yang, Ciqing; Qiao, Liang; Li, Qiuling; Wang, Congrui; Yan, Xin; Lin, Juntang
Abstract: Niemann–Pick disease, type C1 (Npc1), is an atypical lysosomal storage disorder caused by autosomal recessive inheritance of mutations in Npc1 gene. In the Npc1 mutant mice (Npc1 −/− ), the initial manifestation is enlarged spleen, concomitant with free cholesterol accumulation. Telocytes (TCs), a novel type of interstitial cell, exist in a variety of tissues including spleen, presumably thought to be involved in many biological processes such as nursing stem cells and recruiting inflammatory cells. In this study, we found that the spleen is significantly enlarged in Npc1 −/− mice, and the results from transmission electron microscopy examination and immunostaining using three different TCs markers, c‐Kit, CD34 and Vimentin revealed significantly increased splenic TCs in Npc1 −/− mice. Furthermore, hematopoietic stem cells and macrophages were also elevated in Npc1 −/− spleen. Taken together, our data indicate that splenic TCs might alleviate the progress of splenic malfunction via recruiting hematopoietic stem cells and macrophages.